2011
DOI: 10.1002/anie.201100835
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization by Strain‐Promoted Alkyne–Azide Click Reactions

Abstract: alkynes · azides · click chemistry · surface chemistry · surface functionalizationFunctionalization of surfaces becomes increasingly important given the ever-decreasing size of active devices and the concomitant increase in surface-to-volume ratios. As a result, efficient routes for such functionalizations through the attachment of functional monolayers or multilayers have become the focus of much research in the last decade, both for hard (typically inorganic) and soft (polymeric, dendritic) surfaces. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 16 publications
0
81
0
Order By: Relevance
“…[3] Since its discovery,t he SPAAC reaction has been used for the synthesis and/or modification of many materials, including dendrons and dendrimers, [4] topological polymers, [5] organo-micellesa nd liposomes, [6,7] micro-and nanoparticles, [8][9][10][11][12] as well as other materials urfaces. [13][14][15][16] More recently,T sukruk and co-workers prepared branched polyhedral oligomeric silsesquioxane nanoparticles by the interfacial SPAAC reaction. [17] Yi and co-workers reportedc hitosan-poly(ethylene glycol) microparticles featuring azadibenzocyclooctynes (ADIBO) and their potential to undergo bioconjugation in the SPAAC reactionw ith azide-modified proteins and antibodies to afford biosensing platforms.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Since its discovery,t he SPAAC reaction has been used for the synthesis and/or modification of many materials, including dendrons and dendrimers, [4] topological polymers, [5] organo-micellesa nd liposomes, [6,7] micro-and nanoparticles, [8][9][10][11][12] as well as other materials urfaces. [13][14][15][16] More recently,T sukruk and co-workers prepared branched polyhedral oligomeric silsesquioxane nanoparticles by the interfacial SPAAC reaction. [17] Yi and co-workers reportedc hitosan-poly(ethylene glycol) microparticles featuring azadibenzocyclooctynes (ADIBO) and their potential to undergo bioconjugation in the SPAAC reactionw ith azide-modified proteins and antibodies to afford biosensing platforms.…”
Section: Introductionmentioning
confidence: 99%
“…The high mutual reactivity of reaction components, yet (relative) inertness for a large repertoire of other molecular functionalities, explains the fast-growing popularity of strainpromoted cycloadditions for application in material sciences 2 , surface functionalization 3 , bioconjugation 4 , chemical biology and even in vivo use (known as bioorthogonal chemistry) 5,6 .…”
mentioning
confidence: 99%
“…As one of the most effective, site-specific reactions that are tolerant to water, oxygen, and a wide range of functionalities, azide-alkyne cycloaddition (AAC, click chemistry), [14, 1625] especially copper-free click chemistry, has been a promising method for functionalizing bio-related systems. [14, 22, 23] It was also reported that the triazole rings resulting from click chemistry could imitate amide bonds serving as mechanical strength improving moieties. [20, 26] Herein, click chemistry was introduced into CABEs to serve a dual role and create a novel material chemistry design strategy to simultaneously improve the bulk material mechanical strength and enable easy surface site-specific biofunctionalization, which can also be broadly applied to other functional biodegradable polymer design…”
mentioning
confidence: 99%